Bond behaviour of concrete elements strengthened with NSM CFRP laminate strips under wet-dry cycles - Sena-Cruz, José (2012)
In the last years, the near-surface mounted (NSM) technique has been adopted to increase the load carrying capacity of concrete members. Up to now, research was mainly focused on the structural aspects of NSM strengthening of concrete structures. From an extensive bibliographic search performed, no significant information was found concerning to the NSM long-term performance. The present work has the main objective to contribute for the knowledge on durability performance of the NSM technique with CFRP lami-nates submitted to wet-dry cycles by means of direct pullout tests. The influence of the bond length, the groove width and depth, and the number of wet-dry cycles on the bond performance were the main parame-ters analyzed. Thirty five cubic specimens were tested. Digital image correlation method was used, as a com-plementary tool for monitoring the NSM pullout tests. The tests are described, and the obtained results are presented and discussed.